Nutmeg (Myristica fragransI) Farming Development Strategy in Kodeoha Sub-district, North Kolaka Regency - Sariana; Lukman Yunus; Hidrawati (International Journal of Technology and Education Research, 2025)
This research aims to determine the strategy for developing nutmeg (Myristica fragrans) farming in Kodeoha Kistrict, North Kolaka Regency. Determining the research location was carried using simple random sampling with a total of 52 respondents. The analytical tool used is SWOT analysis (strengths, weaknesses, opportunities, threats). Based on the results of the study, the results of the coordinate point of the internal factor were 1.11 and the coordinate point of the external factor werw 1.78. It can be seen that the position of nutmeg farming is in quadrant I which shows that nutmeg farming is in a favorable situation. Pineapple farming has opportunities and strengths so that they can use their strengths and take advantage of existing opportunities. The strategy that must be applied in this condition is to support an aggressive growth policy. In quadrant I of the SO strategy, utilizes transportation facilities and infrastructure to expand the marketing area, maximize promotion of products that are already known and unitize government support to reduce competition for similar products